Design and Analysis of an Interoperable HLA-based Simulation System over a Cloud Environment - Liu, Dan (Université d'Ottawa / University of Ottawa, 2017)
Distributed simulation over Cloud environment is still a new subject. Cloud computing is expected to bring new benefits to conventional distributed simulation, including elasticity on computation resource, cost saving on investment and convenience on service accessibility. A few researches have been done on applying Cloud computing on distributed simulation. However, there are various drawbacks and limitations on those works. Lack of interoperability across Cloud platforms is one of critical drawbacks among them. It can greatly limit the usability and flexibility of distributed simulation over Cloud environment. Based on the investigation on Cloud computing and existing distributed simulation systems over Cloud environment, a novel interoperable HLA-based (High Level Architecture) simulation system over a Cloud environment, ISSC (Interoperable Simulation System over a Cloud Environment), is proposed in this thesis. ISSC aims to address the interoperability issue of simulation system across various Cloud platforms. It employs OCCI and a set of technologies, including Ruby on Rails, OpenVPN and RESTful web services, to build the interoperability across Cloud platforms. It adopts a distributed architecture to construct flexibility and expansibility of the system. The prototype and related experiments performed provides an excellent demonstration that ISSC is a reliable and effective solution on interoperable simulation system over a diverse Cloud environment.
Keywords: HLA, Distributed simulation, Cloud computing, Interoperability